Presupposition dalam Teka-Teki Tradisional Batak Toba - Sidabalok, Dindasari; Mahriyuni, Mahriyuni; Widayati, Dwi (Universitas Indraprasta PGRI, 2025)
This study aims to describe the types of presupposition and how the presupposition occurs in the TB Traditional Riddle. This study uses an ethnographic approach. The data of this study is divided into oral and written data. Oral data were obtained through observation and in-depth interviews with informants. The interview involved 3 informants who met the criteria described by (Spradley, 1979). The questions asked included descriptive questions, structural questions and contrast questions. The written data for this study is sourced from a book entitled Huling-Hulingan and Torkan-Torkanan by (Sibarani, 1995). The data analysis model used also refers to the method proposed by Spradley, making domain analysis, making taxonomic analysis, and making component analysis. The results show that the traditional TB riddle includes the types of existential, lexical, structural, factive, non-factive and counterfactual presuppositions. Presupposition is something abstract that bridges between the speaker's speech and the reaction/answer of the listener. The entire process is within the scope of the context that overshadows every speech situation. The effect of this context can cause single presuppositions, double presumptions, and vague presumptions in the listener/respondent. Context also influences the listener in making an answer from one or more presuppositions that arise in his or her mind.